2020
DOI: 10.1007/s00787-020-01474-y
|View full text |Cite
|
Sign up to set email alerts
|

A short note on the reliability of perceptual timing tasks as commonly used in research on developmental disorders

Abstract: Objectives Perceptual timing tasks are frequently applied in research on developmental disorders, but information on their reliability is lacking in pediatric studies. We therefore aimed to assess the reliability of the four paradigms most frequently used, i.e., time discrimination, time estimation, time production, and time reproduction. Methods Based on the data from our recent longitudinal study by Marx et al. (Front Hum Neurosci 11:122, 2017), we estimated the internal consistency and test-retest reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“… Bluschke et al, 2018 ; Gongsook et al, 2014 ). In this regard, the method of time estimation and the measure accuracy score appear to be particularly robust in terms of their high reliability ( Marx et al, 2021 ). Earlier findings suggest that methylphenidate has a specific effect on improving timing deficits in ADHD ( Smith et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… Bluschke et al, 2018 ; Gongsook et al, 2014 ). In this regard, the method of time estimation and the measure accuracy score appear to be particularly robust in terms of their high reliability ( Marx et al, 2021 ). Earlier findings suggest that methylphenidate has a specific effect on improving timing deficits in ADHD ( Smith et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We validated two instruments that could be effectively used for determining consistent response patterns in reaction time and time estimation research. Other authors have also shown that the process of time estimation represents a paradigm in terms of the reliability of the required tasks [38].…”
Section: The Study Implicationsmentioning
confidence: 99%
“…Recent years show an increased interest in exploring individual differences in children's time awareness (Marx et al, 2020;Labrell et al, 2020). Time awareness, also referred to as time perception, timing, or temporal processing, is believed to facilitate our ability to predict, anticipate, and respond competently to daily life and contribute to the development of children's independence in daily living (Barkley, 1997b;Janesl€ att, 2009;Piaget, 2013).…”
Section: Introductionmentioning
confidence: 99%